Redescription of Paragaleus tengi (Chen, 1963) (Carcharhiniformes: Hemigaleidae) and first record of Paragaleus randalli Compagno, Krupp & Carpenter, 1996 from the western North Pacific - White, William T.; Harris, Mark (Zootaxa, 2013)
Paragaleus tengi was previously considered to be the only member of this genus occurring in the Western Pacific, with Paragaleus randalli occurring in the Indian Ocean and allopatric in distribution. Recent molecular and morphological studies showed that P. randalli also occurs in the Western Pacific with records from Thailand, Malaysia and Indonesia previously mostly incorrectly attributed to P. tengi. This paper provides a redescription of P. tengi and confirms the presence of P. randalli from off Taiwan in the western North Pacific. These two species are morphologically very similar in appearance but differ in meristics, dentition, some coloration attributes and minor morphological characters. The conservation status of these two species needs to be reassessed based on this new information.